Game Theory and Cumulative Voting for Corporate Directors - Glasser, Gerald J. (Management Science, 1959)
Game theory may be used to describe and to analyze corporate elections which are based upon a system of cumulative voting. In these games a strategy is a partition of one's votes among a slate of candidates. A minimax strategy is such a partition which guarantees a voter a certain security level in terms of the number of directorships he can win irrespective of how his opponents vote. These minimax strategies, although not so called, are equivalent to decision rules on how to vote found throughout the literature of business organization.